The translational science promotion and research capacity (T-SPARC) framework: Developing institutional capacity for translational science - Jessica Sperling; Stella Quenstedt; Kristine Glauber; Perusi B. Muhigaba; Eman Ghanem; Tarun Saxena; Vonda Rodriguez; Cinthia Sanchez; F. Joseph McClernon (Journal of Clinical and Translational Science)
Recent years have seen increasing focus, including by the National Institutes for Health (NIH), on developing the field of translational science (TS). TS focuses on improving the process of translational research (TR), including generating knowledge that can facilitate TR across specific diseases or translational stages. With TS as an emerging field, research organizations have an increasing need to understand how to develop capacity for and support the advancement of TS. To support such institutional and infrastructural change, this paper outlines a Translational Science Promotion and Research Capacity (T-SPARC) Framework. The T-SPARC Framework provides a foundation to 1) inform the development of TS-creating and science-supporting interventions and programs, and 2) examine the effectiveness of said interventions and programs. The framework outlines organizational levels that T-SPARC programs can target; mechanisms, or intervention activities, that can foster change; and outcomes, including specific attitudinal or behavioral changes, institutional changes, and domains on which TS changes can focus. T-SPARC’s capacity-building focus builds upon earlier efforts focused on conceptualizing and defining TS. T-SPARC supports movement towards TS goals of reducing longstanding challenges in the TR process, thus accelerating the health impact of TR, and ultimately improving health outcomes.